A Rapid and Sensitive Strip‐Based Quick Test for Nerve Agents Tabun, Sarin, and Soman Using BODIPY‐Modified Silica Materials. Issue 32 (30th May 2016) - Climent, Estela; Biyikal, Mustafa; Gawlitza, Kornelia; Dropa, Tomáš; Urban, Martin; Costero, Ana M.; Martínez‐Máñez, Ramón; Rurack, Knut
Abstract: Test strips that in combination with a portable fluorescence reader or digital camera can rapidly and selectively detect chemical warfare agents (CWAs) such as Tabun (GA), Sarin (GB), and Soman (GD) and their simulants in the gas phase have been developed. The strips contain spots of a hybrid indicator material consisting of a fluorescent BODIPY indicator covalently anchored into the channels of mesoporous SBA silica microparticles. The fluorescence quenching response allows the sensitive detection of CWAs in the μg m −3 range in a few seconds. Abstract : Test strips sense the toxic : Spots of a hybrid indicator material consisting of a fluorescent BODIPY probe covalently anchored into the channels of mesoporous SBA silica microparticles on a test strip detect chemical warfare agents (CWAs; GA=Tabun, GB=Sarin, GD=Soman). The fluorescence quenching response allows the sensitive detection of CWAs in the μg m −3 range in a few seconds.